UJI AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN LEUNCA (Solanum nigrum L.) TERHADAP PERTUMBUHAN JAMUR Candida albicans DAN Microsporum gypseum - Davina Rustyasari; Lanny Mulqie; Siti Hazar (UNISBA Press, 2023)
Abstract. The leunca plant (Solanum nigrum L.) is one of the local plants that is often used as an herbal plant. Leunca leaves contain antifungal secondary metabolites. The purpose of this study was to determine the antifungal activity of the ethanol extract of leunca leaves on the growth of Candida albicans and Microsporum gypseum, and to determine the diameter of the inhibition zone of the ethanol extract of leunca leaves on the growth of Candida albicans and Microsporum gypseum. With the good diffusion method, it was carried out using 4 concentration variations of 10%, 5%, 2.5%, and 1.5%. Negative control (-) contains DMSO and positive control (+) contains 2% ketoconazole. Determination of the diameter of the inhibition zone by looking at the clear zone formed around the wells. The results of the diffusion method test showed that the average diameter of the inhibition zone for Candida albicans growth at various concentrations, namely 10%, 5%, 2.5%, and 1.5%, was 17.45 mm, 14.20 mm, 11.70 mm. and 10.65mm. Meanwhile, the diameter of the inhibition zone for Microsporum gypseum growth was 16.45 mm, 14.35 mm, 13.35 mm and 11.75 mm respectively. The conclusion of this study is that the ethanol extract of leunca leaves is able to inhibit the growth of Candida albicans and Microsporum gypseum fungi. Abstrak. Tanaman leunca (Solanum nigrum L.) adalah salah satu tanaman lokal yang sering digunakan sebagai tanaman herbal. Daun leunca mengandung senyawa metabolit sekunder antijamur. Tujuan penelitian ini untuk mengetahui aktivitas antijamur ekstrak etanol daun leunca terhadap pertumbuhan Candida albicans dan Microsporum gypseum, serta mengetahui diameter zona hambat dari ekstrak etanol daun leunca terhadap pertumbuhan Candida albicans dan Microsporum gypseum. Dengan metode difusi sumuran dilakukan dengan menggunakan 4 variasi konsentrasi 10%, 5%, 2,5%, dan 1,5%. Kontrol negatif (-) berisi DMSO dan kontrol positif (+) berisi ketokonazol 2%. Penentuan diameter zona hambat dengan melihat zona bening yang terbentuk di sekitar sumuran. Hasil pengujian metode difusi menunjukkan rata-rata diameter zona hambat pertumbuhan jamur Candida albicans pada berbagai konsntrasi yaitu 10%, 5%, 2,5%, dan 1,5% adalah 17,45 mm, 14,20 mm, 11,70 mm dan 10,65 mm. Sedangkan diameter zona hambat pertumbuhan jamur Microsporum gypseum secara berurutan adalah 16,45 mm, 14,35 mm, 13,35 mm dan 11,75 mm. Kesimpulan dari penelitian ini yaitu ekstrak etanol daun leunca mampu menghambat pertumbuhan jamur Candida albicans dan Microsporum gypseum.